Lithium-rich manganese-based positive electrode material coated with fast ion conductor and preparation method and application of lithium-rich manganese-based positive electrode material
Patent Information
- Application Number
- CN202411457348.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-14
AI Technical Summary
例如,元素在表面的溶解析出以及包覆层的不稳定性会影响活性物质的性能表现,尽管改善了界面反应,却可能引入新的挑战
[0053] The present invention adopts Li y Sc z Ti a (PO 4 ) 3 Coating the lithium-rich manganese-based cathode material can not only alleviate the cracking of secondary particles and the transformation of the lattice structure, but also form a three-dimensional lithium ion diffusion channel on the surface, reduce the electrode-electrolyte interface impedance, and effectively inhibit the direct contact between the active material and the electrolyte. Contact reduces the occurrence of mechanical microstrain and side reactions, thereby stabilizing the structure of the material and improving the cycle stability and rate performance of lithium-rich manganese-based cathode materials.
Smart Images

Figure BDA0005090854740000131 
Figure BDA0005090854740000141
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries and relates to a fast ion conductor-coated lithium-rich manganese-based positive electrode material and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have become the preferred power source for various 3C products, power tools and electric vehicles due to their high energy and high power density. High energy density lithium-ion batteries are an important development direction in the future energy storage field. At present, the energy density of lithium-ion batteries is mainly restricted by the positive electrode materials, and the development of high voltage and high specific capacity positive electrode materials is a crucial link. Among the ternary positive electrode materials that are regarded as the most promising, with the continuous increase in the price of cobalt and the scarcity of cobalt resources, existing technologies have turned their attention to the direction of cobalt-free, so as to reduce the production cost of materials without affecting the electrochemical performance.
[0003] Lithium-rich manganese-based positive electrode material aLi2MnO3·(1-a)LiMO2 (M=one or more of Ni, Mn, Al, V, Cr, Fe, Ti) has a high discharge specific capacity (>250mAh / g), a high operating voltage (>3.5V), good thermal stability, a wide range of charge and discharge voltage thresholds and a low price. It is not easily restricted by mineral resources and is environmentally friendly. It has become a research hotspot and is an ideal choice for the new generation of high-energy-density power lithium batteries.
[0004] Although lithium-rich manganese-based cathode materials have high specific capacity, there are many problems in their application, such as low initial coulombic efficiency (<80%), obvious voltage and capacity decay during the cycle, and low lithium ion conductivity (10 -13 ~10 -18 cm 2 / s) and high diffusion barriers result in unsatisfactory rate performance of the material, which greatly hinders its commercial development.
[0005] Therefore, in order to further improve the energy density and electrochemical performance of lithium-rich manganese-based positive electrode materials, it is necessary to optimize the electrode materials through modification strategies. In the prior art, the methods mainly use element doping and traditional metal coating strategies to enhance material performance. Although these methods have achieved certain success, they have not effectively solved the problem of side reactions on the surface of electrode materials. For example, the dissolution and precipitation of elements on the surface and the instability of the coating layer will affect the performance of the active material. Although the interfacial reaction is improved, new challenges may be introduced. Therefore, the solid-liquid interface problem of the battery still needs to be further improved to improve the rate performance of the electrode material.
[0006] Based on the above research, there is a need to provide a fast ion conductor coated lithium manganese-based positive electrode material, which can effectively solve the problem of side reactions on the surface of the positive electrode material and avoid the dissolution and precipitation of elements on the surface. At the same time, its coating layer is stable and will not affect the performance of the active substance. Summary of the invention
[0007] The purpose of the present invention is to provide a fast ion conductor coated lithium-rich manganese-based positive electrode material and a preparation method and application thereof. The fast ion conductor coated on the surface of the lithium-rich manganese-based positive electrode material can not only protect the core material from corrosion by the electrolyte and improve the stability of the material, but also form a three-dimensional lithium ion diffusion channel on the surface of the core, thereby greatly improving the rate performance and cycle performance of the material.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a fast ion conductor coated lithium-rich manganese-based positive electrode material, wherein the fast ion conductor coated lithium-rich manganese-based positive electrode material comprises a core and a coating layer on the surface of the core;
[0010] The core includes LiNi x Mn 1-x O2, where 0.1≤x≤0.45;
[0011] The coating layer includes a fast ion conductor, and the fast ion conductor includes Li y Sc z Ti a (PO4)3, where 1≤y≤1.8, 0<z≤0.8, 1≤a≤1.9.
[0012] The present invention adopts Li y Sc z Ti a (PO4)3 coated lithium-rich manganese-based positive electrode material, because LiTi2(PO4)3 has the most suitable three-dimensional framework for lithium ion conduction, and it is a fast ion conductor of NASICON structure, has the advantages of high lithium ion conductivity and stable bulk structure, and also has a good adaptability to the lithium-rich manganese-based positive electrode material. The present invention adopts Sc 3+ Partially replace Ti in LiTi2(PO4)3 4+ After that, the gap Li can be increased +The number of lithium ions can be increased, thereby improving the lithium ion conductivity of the fast ion conductor. Therefore, the coating layer of the present invention can not only alleviate the rupture of the secondary particles and the transformation of the lattice structure, but also form a three-dimensional lithium ion diffusion channel on the surface, reduce the electrode-electrolyte interface impedance, effectively inhibit the direct contact between the active material and the electrolyte, reduce the occurrence of mechanical microstrain and side reactions, thereby stabilizing the structure of the material and improving the cycle stability and rate performance of the lithium-rich manganese-based positive electrode material.
[0013] The core includes LiNi x Mn 1-x O2, wherein 0.1≤x≤0.45, for example, 0.1, 0.2, 0.3, 0.4 or 0.45, the coating layer includes a fast ion conductor, and the fast ion conductor includes Li y Sc z Ti a (PO4)3, wherein 1≤y≤1.8, for example, it can be 1, 1.2, 1.4, 1.6 or 1.8, 0<z≤0.8, for example, it can be 0.1, 0.3, 0.5, 0.7 or 0.8, 1≤a≤1.9, for example, it can be 1, 1.2, 1.4, 1.6, 1.8 or 1.9, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0014] The present invention further includes a transition layer between the core and the coating layer, and the transition layer is a two-phase transition layer of the core and the coating layer.
[0015] Preferably, the coating layer further comprises a manganese ion capture agent.
[0016] Since the core of the present invention is a lithium-rich manganese-based positive electrode material, there is a problem that manganese ions are easily dissolved. Therefore, in order to solve the problem of manganese ion dissolution, the present invention also adds a manganese ion capture agent to the coating layer to capture manganese ions and inhibit the dissolution of manganese ions, thereby further improving the stability and cycle performance of the material.
[0017] Preferably, the manganese ion capture agent comprises a crown ether compound.
[0018] The principle of the manganese ion capture agent of the present invention to capture manganese ions is to coordinate with manganese ions. The present invention adopts crown ether compounds that are easy to coordinate with manganese ions, so as to capture manganese ions more accurately and effectively.
[0019] Preferably, the crown ether compound includes any one of 12-crown-4, 15-crown-5 or 18-crown-6, or a combination of at least two of them.
[0020] Preferably, the particle size D50 of the inner core is 6-8 μm, for example, 6 μm, 7 μm or 8 μm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0021] Preferably, the coating layer has a thickness of 2-20 nm, for example, 2 nm, 5 nm, 10 nm, 15 nm or 20 nm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0022] Preferably, in the lithium-rich manganese-based positive electrode material coated with the fast ion conductor, the content of the coating layer is 1-7wt%, for example, it can be 1wt%, 3wt%, 5wt% or 7wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0023] Preferably, in the coating layer, the content of the fast ion conductor is 70-90 wt%, for example, 70 wt%, 80 wt% or 90 wt%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0024] The content of the fast ion conductor in the coating layer of the present invention is 70-90wt%, and the rest is a manganese ion capture agent. If the content of the fast ion conductor is too high, the manganese ion capture agent cannot effectively play its role. If the content of the fast ion conductor is too low, it will affect the transmission of lithium ions and reduce the overall stability and rate performance of the material.
[0025] In a second aspect, the present invention provides a method for preparing a lithium-rich manganese-based positive electrode material coated with a fast ion conductor as described in the first aspect, the preparation method comprising the following steps:
[0026] LiNi x Mn 1-x O2, a fast ion conductor and a solvent are mixed and dried to obtain a lithium-rich manganese-based positive electrode material coated with the fast ion conductor;
[0027] Or LiNi x Mn 1-x O2, raw materials for preparing the fast ion conductor and a solvent are mixed, dried and sintered to obtain the lithium-rich manganese-based positive electrode material coated with the fast ion conductor.
[0028] The invention can directly coat the fast ion conductor or in-situ coat the fast ion conductor. The preparation method of the invention is easy, low-cost, simple to operate, non-toxic and harmless, and can be applied to large-scale industrial production.
[0029] The fast ion conductor Li y Sc z Ti a The preparation method of (PO4)3 comprises the following steps:
[0030] A lithium source, a scandium source, a titanium source and a phosphorus source are mixed, and then sintered in an oxygen atmosphere at a temperature of 600-1000°C, for example, 600°C, 800°C or 1000°C, for 12-16h, for example, 12h, 14h or 16h, but not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0031] Preferably, the raw materials for preparing the fast ion conductor include a lithium source, a titanium source, a scandium source and a phosphorus source.
[0032] Preferably, the solvent includes any one of methanol, ethanol or propanol, or a combination of at least two of them.
[0033] Preferably, the LiNi x Mn 1-x The solid-liquid ratio of O2 to the solvent is (1-5g):20mL, for example, it can be 1g:20mL, 2g:20mL, 3g:20mL, 4g:20mL or 5g:20mL, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] Preferably, the LiNi x Mn 1-x When O2, fast ion conductor and solvent are mixed, a manganese ion capture agent is also added.
[0035] Preferably, the LiNi x Mn 1-x The method of mixing O2, fast ion conductor and solvent includes heating and stirring to remove the solvent, and the amount of removed solvent accounts for 70-85vol% of the total solvent. For example, it can be 70vol%, 75vol%, 80vol% or 85vol%, but is not limited to the listed values. Other values not listed within the numerical range are also applicable.
[0036] The present invention first heats and stirs to remove most of the solvent, and the amount of the removed solvent is 70-85 vol% of the total amount of the initially added solvent.
[0037] Preferably, the temperature for removing the solvent by heating and stirring is 55-95°C, for example, 55°C, 75°C, or 95°C, but not limited to the listed values, and other values not listed within the numerical range are also applicable, preferably 75-85°C, and the time for removing the solvent by heating and stirring is 4-10h, for example, 4h, 6h, 8h or 10h, but not limited to the listed values, and other values not listed within the numerical range are also applicable, preferably 5-6h.
[0038] Preferably, the drying comprises vacuum drying at 50-120°C, for example, 50°C, 70°C, 90°C, 110°C or 120°C for 6-16h, for example, 6h, 10h, 14h or 16h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0039] The present invention converts LiNi x Mn 1-x When the raw materials and solvents for preparing the fast ion conductor are mixed, dried and sintered, the mixing and drying methods are the same as those for preparing the LiNi x Mn 1-x O2, fast ion conductor and solvent are mixed and dried in the same manner, but grinding is performed between drying and sintering, the grinding time is 10-20 min, for example, 10 min, 15 min or 20 min, the sintering is performed in an oxygen atmosphere, the sintering temperature is 600-1000°C, for example, 600°C, 800°C or 1000°C, the time is 12-16h, for example, 12h, 14h or 16h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0040] Preferably, the LiNi is prepared x Mn 1-x The method of O2 comprises the following steps:
[0041] The lithium source is mixed with the precursor material and calcined to obtain the LiNi x Mn 1-x O2.
[0042] Preferably, the lithium source includes any one of lithium hydroxide, lithium carbonate or lithium nitrate, or a combination of at least two of them.
[0043] Preferably, the calcination includes first firing at 300-500°C, such as 300°C, 400°C or 500°C, for 2-5h, such as 2h, 4h or 5h, and then firing at 650-950°C, such as 650°C, 850°C or 950°C, for 12-16h, such as 12h, 13h or 16h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0044] Preferably, the molar ratio of Li in the lithium source to the total content of nickel and manganese in the precursor material is (1-1.5):1, for example, it can be 1:1, 1.3:1 or 1.5:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0045] Preferably, the method for preparing the precursor material comprises the following steps:
[0046] The nickel-manganese mixed metal source solution, the precipitant solution and the complexing agent solution are subjected to a co-precipitation reaction to obtain the precursor material.
[0047] Preferably, the pH of the coprecipitation reaction is 8-12, for example, 8, 10 or 12, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0048] Preferably, the concentration of the complexing agent in the coprecipitation reaction system is 2-10 mol / L, for example, 2 mol / L, 5 mol / L, 7 mol / L or 10 mol / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0049] Preferably, the nickel-manganese mixed metal source solution includes any one of sulfate, chloride, nitrate or acetate or a combination of at least two thereof, and the molar ratio of nickel to manganese elements is (0.1-0.45):(0.55-0.90), for example, it can be 0.1:0.90, 0.2:0.8, 0.3:0.7 or 0.45:0.90, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0050] Preferably, the precipitant solution comprises a sodium hydroxide solution, and the complexing agent comprises an ammonia solution.
[0051] In a third aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises a lithium-rich manganese-based positive electrode material coated with a fast ion conductor as described in the first aspect.
[0052] Compared with the prior art, the present invention has the following beneficial effects:
[0053] The present invention adopts Li y Sc z Ti a (PO4)3 coated lithium-rich manganese-based positive electrode materials can not only alleviate the rupture of secondary particles and the transformation of lattice structure, but also form three-dimensional lithium ion diffusion channels on the surface, reduce the electrode-electrolyte interface impedance, effectively inhibit the direct contact between active substances and electrolytes, reduce the occurrence of mechanical microstrain and side reactions, thereby stabilizing the structure of the material and improving the cycle stability and rate performance of lithium-rich manganese-based positive electrode materials. DETAILED DESCRIPTION
[0054] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0055] Example 1
[0056] This embodiment provides a fast ion conductor coated lithium-rich manganese-based positive electrode material, the fast ion conductor coated lithium-rich manganese-based positive electrode material comprises a core and a coating layer on the surface of the core, the core is LiNi 0.3 Mn 0.7 O2, the coating layer includes a fast ion conductor and a manganese ion capture agent, and the fast ion conductor is Li 1.2 Sc 0.2 Ti 1.8 (PO4)3, the manganese ion capture agent is 12-crown ether-4;
[0057] The particle size D50 of the core is 7 μm, and the thickness of the coating layer is 10 nm; in the lithium-rich manganese-based positive electrode material coated with the fast ion conductor, the content of the coating layer is 3 wt%; in the coating layer, the content of the fast ion conductor is 80 wt%;
[0058] The method for preparing the fast ion conductor coated lithium-rich manganese-based positive electrode material comprises the following steps:
[0059] (1) mixing lithium carbonate, titanium dioxide, scandium oxide and phosphoric acid according to the formula, and then sintering them at a temperature of 700° C. for 12 hours in an oxygen atmosphere, and grinding them after sintering to obtain the fast ion conductor;
[0060] (2) According to the formula, 3.0 mol NiSO4·6H2O, 7.0 mol MnSO4·H2O and water are uniformly mixed to form a nickel-manganese mixed metal source solution with a total metal ion concentration of 2.5 mol / L, and the nickel-manganese mixed metal source solution, 9 mol / L sodium hydroxide solution and 5 mol / L ammonia water are respectively introduced into a reactor, and a coprecipitation reaction is carried out at a pH of 10.5 and an ammonia concentration of 5 mol / L, and a precursor material is obtained after washing and drying;
[0061] (3) According to the molar ratio of Li:(Ni+Mn)=1.15:1, 10.5 mol of lithium nitrate was weighed, 10 mol of the precursor material prepared in step (2) was mixed evenly with lithium nitrate, and the mixture was sintered at 450°C for 4 h, and then sintered at 850°C for 14 h to obtain a lithium-rich manganese-based positive electrode material LiNi 0.3 Mn 0.7 O2;
[0062] (4) According to the formula, LiNi 0.3 Mn 0.7 O2, fast ion conductor and ethanol are mixed, among which LiNi 0.3 Mn 0.7The solid-liquid ratio of O2 to ethanol is 3.33g:20mL. After heating and stirring at 85°C for 5 hours, 80vol% of the ethanol is removed, and then vacuum dried at 100°C for 10 hours under a vacuum degree of -0.1Mpa to obtain the lithium-rich manganese-based positive electrode material coated with the fast ion conductor.
[0063] Example 2
[0064] This embodiment provides a fast ion conductor coated lithium-rich manganese-based positive electrode material, the fast ion conductor coated lithium-rich manganese-based positive electrode material comprises a core and a coating layer on the surface of the core, the core is LiNi 0.4 Mn 0.6 O2, the coating layer includes a fast ion conductor and a manganese ion capture agent, and the fast ion conductor is Li 1.4 Sc 0.5 Ti 1.5 (PO4)3, the manganese ion capture agent is 18-crown ether-6;
[0065] The particle size D50 of the core is 6 μm, and the thickness of the coating layer is 2 nm; in the lithium-rich manganese-based positive electrode material coated with the fast ion conductor, the content of the coating layer is 1 wt%; in the coating layer, the content of the fast ion conductor is 90 wt%;
[0066] The method for preparing the fast ion conductor coated lithium-rich manganese-based positive electrode material comprises the following steps:
[0067] (1) mixing lithium carbonate, titanium dioxide, scandium oxide and phosphoric acid according to the formula, and then sintering them at a temperature of 600° C. for 12 hours in an oxygen atmosphere, and grinding them after sintering to obtain the fast ion conductor;
[0068] (2) According to the formula, NiSO4·6H2O, MnSO4·H2O and water are uniformly mixed to form a nickel-manganese mixed metal source solution with a total metal ion concentration of 2.5 mol / L, and the nickel-manganese mixed metal source solution, 9 mol / L sodium hydroxide solution and 5 mol / L ammonia water are respectively introduced into a reactor, and a coprecipitation reaction is carried out at a pH of 9 and an ammonia concentration of 2 mol / L, and a precursor material is obtained after washing and drying;
[0069] (3) According to the molar ratio of Li:(Ni+Mn)=1.5:1, 10.5 mol of lithium nitrate was weighed, 10 mol of the precursor material prepared in step (2) was mixed evenly with lithium nitrate, and the mixture was sintered at 500°C for 2 h, and then sintered at 950°C for 12 h to obtain a lithium-rich manganese-based positive electrode material LiNi 0.4 Mn 0.6 O2;
[0070] (4) According to the formula, LiNi0.4 Mn 0.6 O2, fast ion conductor and ethanol are mixed, among which LiNi 0.4 Mn 0.6 The solid-liquid ratio of O2 to ethanol is 1g:20mL. After heating and stirring at 95°C for 10 hours, 80vol% of the ethanol is removed, and then vacuum dried at 120°C for 6 hours under a vacuum degree of -0.1Mpa to obtain the lithium-rich manganese-based positive electrode material coated with the fast ion conductor.
[0071] Example 3
[0072] This embodiment provides a fast ion conductor coated lithium-rich manganese-based positive electrode material, the fast ion conductor coated lithium-rich manganese-based positive electrode material comprises a core and a coating layer on the surface of the core, the core is LiNi 0.3 Mn 0.7 O2, the coating layer includes a fast ion conductor and a manganese ion capture agent, and the fast ion conductor is Li 1.2 Sc 0.2 Ti 1.8 (PO4)3, the manganese ion capture agent is 12-crown ether-4;
[0073] The particle size D of the core 50 The coating layer has a thickness of 8 μm and a thickness of 20 nm; the coating layer has a content of 7 wt % in the lithium-rich manganese-based positive electrode material coated with the fast ion conductor; the fast ion conductor content in the coating layer is 70 wt %;
[0074] The method for preparing the fast ion conductor coated lithium-rich manganese-based positive electrode material comprises the following steps:
[0075] (1) mixing lithium carbonate, titanium dioxide, scandium oxide and phosphoric acid according to the formula, and then sintering them at a temperature of 1000° C. for 16 hours in an oxygen atmosphere, and grinding them after sintering to obtain the fast ion conductor;
[0076] (2) According to the formula, 3.0 mol NiSO4·6H2O, 7.0 mol MnSO4·H2O and water are uniformly mixed to form a nickel-manganese mixed metal source solution with a total metal ion concentration of 2.5 mol / L, and the nickel-manganese mixed metal source solution, 9 mol / L sodium hydroxide solution and 5 mol / L ammonia water are respectively introduced into a reactor, and a coprecipitation reaction is carried out at a pH of 12 and an ammonia concentration of 10 mol / L, and a precursor material is obtained after washing and drying;
[0077] (3) According to the molar ratio of Li:(Ni+Mn)=1.1:1, 10.5 mol of lithium nitrate was weighed, 10 mol of the precursor material prepared in step (2) was mixed evenly with lithium nitrate, and the mixture was calcined at 300°C for 5 h, and then calcined at 650°C for 16 h to obtain a lithium-rich manganese-based positive electrode material LiNi 0.3 Mn 0.7 O2;
[0078] (4) According to the formula, LiNi 0.3 Mn 0.7 O2, fast ion conductor and ethanol are mixed, among which LiNi 0.3 Mn 0.7 The solid-liquid ratio of O2 to ethanol is 5g:20mL. The mixture is heated and stirred at 75°C for 10 hours. After removing 75 vol% of the ethanol, the mixture is vacuum dried at 100°C for 16 hours under a vacuum degree of -0.1Mpa to obtain the fast ion conductor-coated lithium-manganese-based positive electrode material.
[0079] Example 4
[0080] This embodiment provides a fast ion conductor coated lithium manganese-rich positive electrode material, which is the same as that of Embodiment 1 except that the content of the coating layer is 0.5wt% and the thickness of the coating layer is adaptively changed.
[0081] Example 5
[0082] This embodiment provides a fast ion conductor coated lithium manganese-rich positive electrode material, which is the same as that of Embodiment 1 except that the content of the coating layer is 9wt% and the thickness of the coating layer is adaptively changed.
[0083] Example 6
[0084] This embodiment provides a fast ion conductor coated lithium manganese-rich positive electrode material. The fast ion conductor coated lithium manganese-rich positive electrode material is the same as that of Embodiment 1 except that the content of the fast ion conductor in the coating layer is 60wt%.
[0085] Example 7
[0086] This embodiment provides a fast ion conductor coated lithium manganese-based positive electrode material. The fast ion conductor coated lithium manganese-based positive electrode material is the same as that of Embodiment 1 except that the content of the fast ion conductor in the coating layer is 95wt%.
[0087] Example 8
[0088] This embodiment provides a fast ion conductor coated lithium-rich manganese-based positive electrode material, and the fast ion conductor coated lithium-rich manganese-based positive electrode material is the same as that of Embodiment 1 except that the coating layer does not include a manganese ion capture agent;
[0089] The method for preparing the fast ion conductor coated lithium-rich manganese-based positive electrode material comprises the following steps:
[0090] (1) According to the formula, 3.0 mol NiSO4·6H2O, 7.0 mol MnSO4·H2O and water are uniformly mixed to form a nickel-manganese mixed metal source solution with a total metal ion concentration of 2.5 mol / L, and the nickel-manganese mixed metal source solution, 9 mol / L sodium hydroxide solution and 5 mol / L ammonia water are respectively introduced into a reactor, and a coprecipitation reaction is carried out at a pH of 10.5 and an ammonia concentration of 5 mol / L, and a precursor material is obtained after washing and drying;
[0091] (2) According to the molar ratio of Li:(Ni+Mn)=1.15:1, 10.5 mol of lithium nitrate was weighed, 10 mol of the precursor material prepared in step (1) was mixed evenly with lithium nitrate, and the mixture was sintered at 450°C for 4 h, and then sintered at 850°C for 14 h to obtain a lithium-rich manganese-based positive electrode material LiNi 0.3 Mn 0.7 O2;
[0092] (3) According to the formula, LiNi 0.3 Mn 0.7 O2, lithium hydroxide, titanium nitrate, scandium nitrate and ethanol are mixed, among which LiNi 0.3 Mn 0.7 The solid-liquid ratio of O2 to ethanol is 3.33g:20mL. After heating and stirring at 85°C for 5 hours, 80vol% of the ethanol is removed, and then vacuum dried at 100°C for 10 hours under a vacuum degree of -0.1Mpa to obtain the lithium-rich manganese-based positive electrode material coated with the fast ion conductor.
[0093] Comparative Example 1
[0094] This comparative example provides a lithium-rich manganese-based positive electrode material, which is the same as Example 1 except that it does not contain a coating layer;
[0095] The lithium-rich manganese-based positive electrode material is different from the LiNi 0.3 Mn 0.7 The preparation method of O2 is the same.
[0096] Comparative Example 2
[0097] This comparative example provides a fast ion conductor coated lithium-rich manganese-based positive electrode material, which is the same as Example 1 except that the fast ion conductor is LiTi2(PO4)3;
[0098] The preparation method of the fast ion conductor coated lithium-rich manganese-based positive electrode material is the same as that of Example 1, except that scandium oxide is not added in step (1).
[0099] The positive electrode materials obtained in the above embodiments and comparative examples are prepared into positive electrode sheets, and then prepared into button batteries. The specific preparation method includes: dropping the positive electrode material, acetylene black and polyvinylidene fluoride into N-methyl-2-pyrrolidone in a mass ratio of 8:1:1 to prepare a solution, and then evenly applying it on aluminum foil, drying and stamping it into a thin sheet; assembling the battery electrode sheet, single lithium sheet, glass fiber diaphragm, electrolyte (LiClO4), gasket, shrapnel and battery shell into a button battery in an argon glove box, and then testing the cycle performance and rate performance of the button battery under 2.0-4.5V, 0.2C conditions.
[0100] The test results are shown in Table 1:
[0101] Table 1
[0102]
[0103]
[0104] From Table 1 we can see that:
[0105] It can be seen from Example 1 and Comparative Example 1 that the coating layer is provided on the surface of the lithium-rich manganese-based material of the present invention, which can effectively improve the cycle performance and rate performance of the battery; it can be seen from Example 1 and Comparative Example 2 that the fast ion conductor coated by the present invention is Li y Sc z Ti a (PO4)3 can increase the Li in the gap of fast ion conductor + The amount of fast ion conductor can be increased, thereby improving the lithium ion conductivity of the fast ion conductor and improving the rate performance of the battery; it can be seen from Example 1 and Examples 4-5 that the content of the coating layer of the present invention will affect the effect of the coating layer; it can be seen from Examples 1 and 6-7 that the content of the fast ion conductor in the coating layer of the present invention will affect the effect of the fast ion conductor and the manganese ion capture agent, thereby affecting the cycle performance and rate performance of the battery; it can be seen from Example 1 and Example 8 that the addition of the manganese ion capture agent in the coating layer of the present invention can improve the stability of the material, thereby improving the cycle performance of the battery.
[0106] In summary, the present invention provides a fast ion conductor coated lithium-rich manganese-based positive electrode material, a preparation method and an application thereof. The fast ion conductor coated on the surface of the lithium-rich manganese-based positive electrode material can not only protect the core material from corrosion by the electrolyte and improve the stability of the material, but also form a three-dimensional lithium ion diffusion channel on the core surface, thereby greatly improving the rate performance and cycle performance of the material.
[0107] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A fast ion conductor coated lithium-rich manganese-based positive electrode material, characterized in that: The fast ion conductor coated lithium-rich manganese-based positive electrode material comprises a core and a coating layer on the surface of the core; The core includes LiNi x Mn 1-x O2, where 0.1≤x≤0.45; The coating layer includes a fast ion conductor, and the fast ion conductor includes Li y Sc z Ti a (PO4)3, where 1≤y≤1.8, 0<z≤0.8, 1≤a≤1.
9.
2. The fast ion conductor coated lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The coating layer also includes a manganese ion capture agent; Preferably, the manganese ion capture agent comprises a crown ether compound; Preferably, the crown ether compound includes any one of 12-crown-4, 15-crown-5 or 18-crown-6, or a combination of at least two of them.
3. The fast ion conductor coated lithium-rich manganese-based positive electrode material according to claim 2, characterized in that: The thickness of the coating layer is 2-20 nm; Preferably, in the lithium-rich manganese-based positive electrode material coated with the fast ion conductor, the content of the coating layer is 1-7wt%; Preferably, the content of the fast ion conductor in the coating layer is 70-90 wt %.
4. A method for preparing a lithium-rich manganese-based positive electrode material coated with a fast ion conductor as claimed in any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: LiNi x Mn 1-x O2, a fast ion conductor and a solvent are mixed and dried to obtain a lithium-rich manganese-based positive electrode material coated with the fast ion conductor; Or LiNi x Mn 1-x O2, raw materials for preparing the fast ion conductor and a solvent are mixed, dried and sintered to obtain the lithium-rich manganese-based positive electrode material coated with the fast ion conductor.
5. The preparation method according to claim 4, characterized in that: The raw materials for preparing the fast ion conductor include a lithium source, a titanium source, a scandium source and a phosphorus source; Preferably, the solvent comprises any one of methanol, ethanol or propanol or a combination of at least two thereof; Preferably, the LiNi x Mn 1-x The solid-liquid ratio of O2 to solvent is (1-5g):20mL.
6. The preparation method according to claim 4 or 5, characterized in that: The LiNi x Mn 1-x When O2, fast ion conductor and solvent are mixed, a manganese ion capture agent is also added; Preferably, the LiNi x Mn 1-x The method of mixing O2, the fast ion conductor and the solvent includes heating and stirring to remove the solvent, wherein the amount of the removed solvent accounts for 70-85 vol% of the total amount of the solvent; Preferably, the drying comprises vacuum drying at 50-120° C. for 6-16 h.
7. The preparation method according to any one of claims 4 to 6, characterized in that: Preparation of the LiNi x Mn 1-x The method of O2 comprises the following steps: The lithium source is mixed with the precursor material and calcined to obtain the LiNi x Mn 1-x O2; Preferably, the calcination comprises first firing at 300-500°C for 2-5h, and then firing at 650-950°C for 12-16h.
8. The preparation method according to claim 7, characterized in that: The method for preparing the precursor material comprises the following steps: The nickel-manganese mixed metal source solution, the precipitant solution and the complexing agent solution are subjected to a co-precipitation reaction to obtain the precursor material.
9. The preparation method according to claim 8, characterized in that: The pH of the coprecipitation reaction is 8-12; Preferably, the concentration of the complexing agent in the coprecipitation reaction system is 2-10 mol / L.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises a lithium-rich manganese-based positive electrode material coated with a fast ion conductor as described in any one of claims 1 to 3.